2011
DOI: 10.1097/brs.0b013e318216ad48
|View full text |Cite
|
Sign up to set email alerts
|

Quebec Back Pain Disability Scale, Low Back Outcome Score and Revised Oswestry Low Back Pain Disability Scale for Patients With Low Back Pain Due to Degenerative Disc Disease

Abstract: QBPDS-PL and RODI-PL are reliable and valid. Furthermore, investigation of the psychometric properties of the LBOS-PL in different spinal conditions is required. There is a relation between the results of the QDS-PL, and different levels of advancement in degenerative disease of the lumbar spine, according to the Modic Classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 28 publications
3
39
0
1
Order By: Relevance
“…We found an excellent, significant correlation between the Hungarian versions of the ODI and QDS (r 0.81) which was similar to the previously published French (0.9) [17], English (0.82) [39] and (0.80) [14] and Polish (0.82) [23] versions of the questionnaires. Greek [31], Turkish [32] and Korean [34] studies reported weaker correlations between the ODI and the QDS (r: 0.78, 0.67 and 0.72, respectively).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We found an excellent, significant correlation between the Hungarian versions of the ODI and QDS (r 0.81) which was similar to the previously published French (0.9) [17], English (0.82) [39] and (0.80) [14] and Polish (0.82) [23] versions of the questionnaires. Greek [31], Turkish [32] and Korean [34] studies reported weaker correlations between the ODI and the QDS (r: 0.78, 0.67 and 0.72, respectively).…”
Section: Discussionsupporting
confidence: 73%
“…The Oswestry Disability Index (ODI) [12,13] and the Quebec Back Pain Disability Scale (QDS) [14,15] are two reliable, valid and widely used PROMs in spine care that have been validated for use with numerous languages since first being reported in English. Validation studies of the Spanish [16], French-Canadian [17], Danish [18], Chinese [19,20], German [21], Korean [22], Polish [23], Italian [24], Persian [25], Finnish [26], Turkish [27], Brazilian-Portuguese [28], Norwegian [29] and Greek [30] versions of the ODI have all been published. Nine validation studies on national versions of the QDS (Greek [31], Turkish [32], Polish [23], Persian [25], Portuguese [33], Korean [34], Dutch [35], French [36] and Arabic [37]) have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…7 The Cronbach ␣ ‡ References 5, 7-10, 14 -18, 21, 23-27, 29 -31, 33, 35, 37, 41-45. § References 5,[8][9][10][14][15][16][17][18]21,[23][24][25][26][27][29][30][31] 33, 35,[41][42][43][44][45][8][9][10]14,15,18,21,23,24,26,27, 29, 30, 35,[41][42][43][44][45] # References 5,9,24,25,27, 31, 35, 37, 44, 45. ** References 5,7,9,16,21,24,25,27, 31, 33, 35, 37, 41,[43][44][45].…”
Section: Reliability Internal Consistencymentioning
confidence: 99%
“…The possible overall rating for a measurement property is "positive," "indeterminate," or "negative," accompanied with a level of evidence ("strong," "moderate," "limited," "conflicting," and "unknown"). To give a positive or negative rating for the results of the measurement properties, criteria for good mea- [15][16][17][18]21,23,[25][26][27] 29, 33,[41][42][43]7,14,24, 30, 31, 35, 37, 44, 45. Meta-analyses were not performed because there were no more than 2 studies per measurement property per language version.…”
Section: Data Synthesis Levels Of Evidence and Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation